Eating behaviour - Dovey, Terence M. (Terence Michael) (McGraw Hill/Open University Press, 2010)
This book is essential reading for psychology and health psychology students, those taking eating behaviour modules, and eating behaviour and disorders courses. It is also valuable reading for nutritionists, food scientists, occupational therapists and medical students.